2016
DOI: 10.4103/2278-330x.179689
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use among the cancer patients in Northern India

Abstract: Background:Cancer has emerged as a major public health problem. People often turn to complementary and alternative medicine (CAM) when they have a long-lasting problem. CAM is a group of diverse medical and healthcare systems, practices, and products that are not generally considered part of conventional medicine. The present study was conducted to find prevalence rate of CAM use among cancer patients undergoing allopathic treatment in a health facility and to compare the CAM usage patterns among different sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 6 publications
(5 reference statements)
5
25
1
1
Order By: Relevance
“…This study also looked into the prevalence of CAM awareness among cancer patients which turned out to be very high (93.0%) as compared to modern treatments (75.0%), and this was in accordance with the results of a similar study reported by Kumar D et al. [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study also looked into the prevalence of CAM awareness among cancer patients which turned out to be very high (93.0%) as compared to modern treatments (75.0%), and this was in accordance with the results of a similar study reported by Kumar D et al. [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…A similar association of CAM use with advanced-stage disease has also been noted in other studies [ 22 ]. Many Indian studies also reported that the prevalence of CAM usage varied with stage and diagnosis, and showed that its use is most common in breast cancer, followed by head and neck malignancy [ 15 ], whereas in western literature, Bahall et al. reported prostate (44.4%) as the most common diagnosis followed by breast (39.6%), colon (38.7%) and ovarian (37.0%) malignancy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis published in 2012 estimated that 40% of cancer survivors worldwide use CTs, though estimates are slightly higher in North American countries (46%) and slightly lower in European countries (34%). 3 Several recent studies published since then have found similarly high rates of CT use 4 - 8 or higher. 1 , 9 - 12 Cancer survivors have reported several reasons for CT use, including alleviating side effects of treatment, improving health/healing/immune function, wanting control, and improving emotional/psychological functioning.…”
Section: Introductionmentioning
confidence: 96%
“…Hence, it can be considered as a good alternative to exercise therapy [3,5]. In addition, it is believed that it can reduce medication use in adults with Type II Diabetes Mellitus [6].…”
Section: Introductionmentioning
confidence: 99%